Dynamics of Botho/Ubuntu in Basotho Folklore: The Relevance of Basotho Folktales in the 21st Century Exemplified by “Leobu” - Mensele, Mary; Khanyetsi, Mabohlokoa (Southern African Journal for Folklore Studies)
This study is triggered by the one description given to botho/ubuntu nowadays. The term botho/ubuntu is often described as a special kind of African humanism, based specifically on one Basotho proverb, Motho ke motho ka batho, which means “a person is a person through other people.” It is associated with positive attributes among African people such as kindness, sincerity and humanness. This article argues that botho/ubuntu can also be described as a multifaceted aspect of human nature that should not be interpreted narrowly or as one-sided, in terms of conformity to goodness and kindness to be accepted or fit within society, because human nature—botho/ubuntu—is not always harmony-seeking. It is human nature for people to be kind and loving as much as it is human nature for people to be jealous, selfish, rebellious, or to lie. Basotho folktales such as “Leobu” have always depicted within the Basotho various characteristics in human beings to make listeners or society aware of different personalities in life, because human nature is a dynamic phenomenon. The study employed a contextual approach to analyse and interpret the Basotho folktale “Leobu” in relation to events and human activities as well as connections with the self, the environment and with other people. A contextual approach will help readers become aware that Basotho folktales are still relevant as a tool for scrutinising people’s actions and to encourage people to interrogate every piece of information they receive, for they may not know the real intentions of those delivering such information.